A new species and new record of the genus Sinocorophium (Crustacea, Amphipoda, Corophiidae) from Korean Waters - Heo, Jun-Haeng; Kim, Young-Hyo (Zootaxa, 2017)
Two species of the genus Sinocorophium belonging to the family Corophiidae were collected from shallow Korean waters. One of the species is new and is described as Sinocorophium jindoense. The new species Sinocorophium jindoense sp. nov. is similar to S. hangangense and S. monospinum. However, the new species can be obviously distinguished from the other two by having a subpointed rostrum. The other species, Sinocorophium homoceratum Yu, 1938 is previously known from Chinese waters. It is a new record from Korean waters. Both species are illustrated and compared to related species. A key to the species of Sinocorophium is also provided.